Overflow and flooding events in the Ronda stream watershed in Ponta Grossa, PR, Brazil (Terr@ Plural, 2021)
Episodes of precipitation are part of the climate variability of a region;however, when associated with impermeability processes of the soils and inefficienturban drainage, they increase the rates of floods and overflows events, which causesevere inconvenience and damage for the population. Thus, this study correlates therecord of 60 occurrences of floods and overflows, in the Ronda stream watershed,located largely in the urban area of the city of Ponta Grossa, between the years 1980and 2017. Half of the occurrences happened due to extreme events, that is, withprecipitation equal to or greater than 50 mm. Many occurrences occurred in areasconsidered to be at risk, mainly in the floodplain of the Ronda stream.
Keywords: Precipitation; Surface runoff; Urban drainage